Formation of Anisotropic Gold Nanoparticles using Wet Chemical Method - Zulkepli, Nor Emelia Diana; Morsin, Marlia; Razali, Nur Liyana; Nafisah, Suratun (Evolution in Electrical and Electronic Engineering, 2021)
This paper presents synthesized gold nanoparticles in nanorods shapes using wet chemical method. The gold nanoparticles forms are classified into spherical shapes and non-spherical shapes. The spherical shapes are basic and commonly synthesize due to its simplicity while non- spherical shapes have their own unique properties. Gold nanorods are one of the non-spherical shapes that highly compliant with the human body, have minimal toxicity, and are adaptable. In this project, wet chemical method namely seed-mediated growth has been used to synthesis gold nanorods. This method is preferred for producing gold nanorods in smaller size, higher yields, and cost less. In this process, during physical observation, the seed solution turned from yellow to light brown while after adding the seed solution into the growth solution, the colour changes to purple colour. Moreover, the molarity of surfactant named cetyl trimethylammonium bromide (CTAB) has been varied with the ranges from 0.1M to 1.0M. There are different colour observed with the variation of surfactant indicated the huge impact of this chemical on the synthesis process. This outcome has been supported by optical and morphological properties. The optical characterization has been observed using the UV-Vis-1800 Shimadzu (Japan) spectrophotometer. The morphology feature of gold nanoparticles was monitored using FESEM, Jeol JSM-7600F Schottky (Japan) with magnification of 100K and voltage acceleration of 5 kV.